Influence of surface coating on the intracellular behaviour of gold nanoparticles: a fluorescence correlation spectroscopy study. Issue 38 (26th September 2017) - Silvestri, A.; Di Silvio, D.; Llarena, I.; Murray, R. A.; Marelli, M.; Lay, L.; Polito, L.; Moya, S. E.
Abstract : Fluorescence correlation spectroscopy allows the correlation of the state of aggregation in vitro with the intracellular fate of gold NPs for different antifouling coatings. Abstract : In the biomedical applications of nanoparticles (NPs), the proper choice of surface chemistry is a crucial aspect in their design. The nature of the coating can heavily impact the interaction of NPs with biomolecules, affect the state of aggregation, and ultimately determine their biological fate. As such, protein corona formation and the aggregation behaviour of gold NPs (Au NPs) are studied here. Au NPs are prepared with four distinct surface functionalisations, namely mercaptosuccinic acid (MSA), N -4-thiobutyroil glucosamine, HS-PEG5000 and HS-alkyl-PEG600 . Corona formation, aggregation, and the intracellular behaviour of the Au NPs are then investigated by means of Fluorescence Correlation Spectroscopy (FCS) in cell culture media and in live cells. To evaluate the state of aggregation and the formation of a protein corona, the Au NPs are incubated in cell media and the diffusion coefficient is determined via FCS. The in vitro behaviour is compared with the level of aggregation of the NPs in cells. Diffusion times of the NPs are estimated at different positions in the cell after a one hour incubation period. It is found that the majority of MSA and glucose-Au NPs are present inside the cell as slowly diffusing species with diffusion times ( τ D ) greater than 6000 μs (hydrodynamic diameter >250 nm). PEGylated Au NPs adsorb a small amount of protein and manifest low agglomeration both in media and in living cells. In particular, the HS-alkyl-PEG600 coating shows an excellent correlation between lower protein adsorption, 4-fold lower compared to the MSA coated NPs, and limited intracellular aggregation. In the case of single HS-alkyl-PEG600 coated NPs, it is found that typical intracellular τ D values range from 500 to 1500 μs, indicating that these particles display reduced aggregation in the intracellular environment.